Effects of microenvironment in osteosarcoma on chemoresistance and the promise of immunotherapy as an osteosarcoma therapeutic modality - Yu, Lei; Zhang, Jian; Li, Yunfeng (Frontiers in Immunology, 2022)
Osteosarcoma (OS) is one of the most common primary malignant tumors originating in bones. Its high malignancy typically manifests in lung metastasis leading to high mortality. Although remarkable advances in surgical resection and neoadjuvant chemotherapy have lengthened life expectancy and greatly improved the survival rate among OS patients, no further breakthroughs have been achieved. It is challenging to treat patients with chemoresistant tumors and distant metastases. Recent studies have identified a compelling set of links between hypoxia and chemotherapy failure. Here, we review the evidence supporting the positive effects of hypoxia in the tumor microenvironment (TME). In addition, certain anticancer effects of immune checkpoint inhibitors have been demonstrated in OS preclinical models. Continued long-term observation in clinical trials is required. In the present review, we discuss the mutualistic effects of the TME in OS treatment and summarize the mechanisms of immunotherapy and their interaction with TME when used to treat OS. We also suggest that immunotherapy, a new comprehensive and potential antitumor approach that stimulates an immune response to eliminate tumor cells, may represent an innovative approach for the development of a novel treatment regimen for OS patients.